Trend 1994 - 2003. Statistics Canada. CANSIM: Environment - Environmental Protection | Country: Canada | Province: Newfoundland and Labrador | Table: Provincial profile of nature parks | Variable: Attendance (number x 1,000) | Units: , 1994-2003. Data-Planet™ Statistical Ready Reference by Conquest Systems, Inc. Dataset-ID: 075-001-084. - Statistics Canada (Data-Planet™ Statistical Ready Reference by Conquest Systems, Inc., 2015)
Statistics Canada (2015). CANSIM: Environment - Environmental Protection | Country: Canada | Province: Newfoundland and Labrador | Table: Provincial profile of nature parks | Variable: Attendance (number x 1,000) | Units: , 1994-2003. Data-Planet™ Statistical Ready Reference by Conquest Systems, Inc. [Data-file]. Dataset-ID: 075-001-084. Dataset: Provides data on measures taken to reduce or prevent environmental impacts in Canada, including expenditures by industry and government. CANSIM is Statistics Canada's key socioeconomic database. The datasets included here provide statistics on the Canadian population, and the nation’s resources, economy, society, and culture. In addition to conducting a Census every five years, approximately 350 active surveys are conducted on virtually all aspects of Canadian life. Statistics are provided for the nation as a whole, provinces, and other subnational geographies where available. Category: Natural Resources and Environment Source: Statistics Canada Established as Canada's central statistical office by the Statistics Act of 1985, Statistics Canada is required to "collect, compile, analyse, abstract and publish statistical information relating to the commercial, industrial, financial, social, economic and general activities and conditions of the people of Canada." Its main objectives are to provide statistical information and analysis about Canada’s economic and social structure and to promote sound statistical standards and practices. http://www.statcan.gc.ca/ Subject: Environment, Environmental Protection